2017
DOI: 10.1371/journal.pone.0178007
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on bio-aerosols in healthcare and the dental environment

Abstract: BackgroundBio-aerosols originate from different sources and their potentially pathogenic nature may form a hazard to healthcare workers and patients. So far no extensive review on existing evidence regarding bio-aerosols is available.ObjectivesThis study aimed to review evidence on bio-aerosols in healthcare and the dental setting. The objectives were 1) What are the sources that generate bio-aerosols?; 2) What is the microbial load and composition of bio-aerosols and how were they measured?; and 3) What is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
279
0
34

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(319 citation statements)
references
References 76 publications
(43 reference statements)
6
279
0
34
Order By: Relevance
“…A review conducted by Zemouri et al (2017) showed that 38 types of microorganisms could be found in the air of the dental clinic, including Legionella pneumophila, the causative agent of severe pneumonia. There have been reports of patients acquiring pneumonia after being treated at a dental clinic (Ricci et al, 2012).…”
Section: Droplets and Aerosols In Dental Settingmentioning
confidence: 99%
“…A review conducted by Zemouri et al (2017) showed that 38 types of microorganisms could be found in the air of the dental clinic, including Legionella pneumophila, the causative agent of severe pneumonia. There have been reports of patients acquiring pneumonia after being treated at a dental clinic (Ricci et al, 2012).…”
Section: Droplets and Aerosols In Dental Settingmentioning
confidence: 99%
“…Usually, splatters and droplets can contaminate a 3-ft diameter range, while aerosols produced can spread further and cause long-lasting contamination and potential transmission (Zemouri, de Soet, Crielaard, & Laheij, 2017). A recent study published in the New England Journal of Medicine demonstrated that aerosol and fomite transmission of SARS-CoV-2 is plausible, since coronavirus remains viable and infectious in aerosols for hours, and on inanimate surfaces up to days (van Doremalen et al, 2020).…”
Section: Protec Tive Me a Sure S To Minimize Saliva-med Iated S Prementioning
confidence: 99%
“…; Zemouri et al . ), and many technologies are used to remove/inactivate such airborne pathogens in healthcare and other settings (Rautemaa et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air is well recognized as a vehicle for the direct and indirect spread of a wide variety of human pathogens (Decraene et al 2008;Sattar et al 2016b;Zemouri et al 2017), and many technologies are used to remove/inactivate such airborne pathogens in healthcare and other settings (Rautemaa et al 2006). We had previously shown a HEPA filter-and UV-light-based indoor air decontamination device to reduce the levels of airborne vegetative Letters in Applied Microbiology 68, 206--211 © 2018 The Society for Applied Microbiology bacteria by ≥3Á0 log 10 (≥99Á9%) in~45 min Sattar et al 2016a;Zargar et al 2016).…”
Section: Introductionmentioning
confidence: 99%